Effects of Reading Motivation and Cultural Text Types on High School Students’ Inferential Reading Skills - Raaomardsingh B Sihombing; Yuyun Yulia; Lusi Nurhayati; Ari Purnawan (LPPM Universitas Advent Indonesia, 2026)
This study investigates the effects of reading motivation and cultural text types on the inferential reading skills of high school students, as well as the interaction between these two variables. A post-test only quasi-experimental design with a 2×2 factorial arrangement was employed. The population comprised 191 Grade 11 students at SMA Negeri 2 Bantul, from which 80 participants were selected through screening. Instrument validity was established using Pearson Product-Moment correlation, with all calculated r-values exceeding the r-table threshold. Reliability was confirmed through Cronbach's Alpha coefficients above 0.80, indicating strong internal consistency. Data were analyzed using Two-Way ANOVA followed by effect size analysis to determine the magnitude of influence of each independent variable on inferential reading skills. The results revealed that reading motivation did not exert a significant effect on inferential reading skills (p = 0.115; d = 0.347, modest effect), whereas cultural text type had a significant effect (p = 0.016; d = 0.546, moderate effect). Students who read local culture texts achieved higher mean scores than those who read popular culture texts. No significant interaction was found between reading motivation and cultural text type. These findings suggest that culturally relevant text selection plays a meaningful role in developing inferential reading skills among EFL students. Accordingly, the integration of culture-based reading materials into EFL classrooms is recommended as a pedagogical strategy to enhance students' inferential comprehension.